Functional characterization of three flavonoid glycosyltransferases from Andrographis paniculata. Issue 6 (12th June 2019) - Li, Yuan; Li, Xin-Lin; Lai, Chang-Jiang-Sheng; Wang, Rui-Shan; Kang, Li-Ping; Ma, Ting; Zhao, Zhen-Hua; Gao, Wei; Huang, Lu-Qi
Abstract : Andrographis paniculata is an important traditional medicinal herb in South and Southeast Asian countries with diverse pharmacological activities that contains various flavonoids and flavonoid glycosides. Glycosylation can transform aglycones into more stable, biologically active and structurally diverse glycosides. Here, we report three glycosyltransferases from the leaves of A. paniculata (ApUFGTs) that presented wide substrate spectra for flavonoid glycosylation and exhibited multi-site glycosylation on the substrate molecules. They acted on the 7-OH position of the A ring and were able to glycosylate several other different types of compounds. The biochemical properties and phylogenetic analysis of these glycosyltransferases were also investigated. This study provides a basis for further research on the cloning of genes involved in glycosylation from A. paniculata and offers opportunities for enhancing flavonoid glycoside production in heterologous hosts. These enzymes are expected to become effective tools for drug discovery and for the biosynthesis of derivatives via flavonoid glycosylation.